A taxonomic revision of western Eupholidoptera bush crickets (Orthoptera: Tettigoniidae): testing the discrimination power of DNA barcode. (30th August 2013) - ALLEGRUCCI, GIULIANA; MASSA, BRUNO; TRASATTI, ALESSANDRA; SBORDONI, VALERIO
Abstract The genus Eupholidoptera includes 46 Mediterranean species distributed from Turkey to Greece, Italy and southern France. In the eastern part of its range, Eupholidoptera has been considered to consist of several distinct species, while in the Balkans and Italian peninsula only E. chabrieri has been recognized. However, the status of some Italian populations, confined to particular geographic areas, remains uncertain. To investigate the delimitation of the Italian taxa of Eupholidoptera, we performed both morphological and molecular analyses. Morphological analysis was carried out by considering diagnostic characters usually used to distinguish different taxa, such as the shape of titillators in males and the subgenital plate in females. Molecular analysis was performed by sequencing three mitochondrial genes: 12S rRNA, 16S rRNA, partially sequenced and the entire gene of cox1. Molecular markers were used to infer phylogenetic relationships among the Italian Eupholidoptera species and to reconstruct the historical processes that shaped their current geographic distribution. Results from both morphological and molecular analyses were used to revise the taxonomic arrangement of species. On the whole we were able to distinguish nine lineages of Italian Eupholidoptera, of which E. tyrrhenicasp.n. from Corsica is described as a new species. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:EBD181A0-5263-4880-AC80-66F624506E3A.